PSXI-23 Effects of stocking rate on body condition of F-1 (Brahman x Hereford or Angus) cows at weaning and rebreeding performance. (7th December 2018) - Rouquette, M; Kerby, J; Norman, K
Abstract: Body condition score (BCS) of cows at weaning, at calving, and at time of rebreeding can affect percent rebreeding and calving interval. During a 26-yr period, 3282 head of average 6.5 yr old F-1 (Brahman x Hereford or Angus) cows that calved in fall (n=1451) or winter (n=1825) were used in stocking rates on pasture. Fall (FAL) calves were born 25 Sept, stocked on ryegrass or clover overseeded on bermudagrass (BG), and weaned 17 June. Winter (WIN) calves were born 14 Feb, stocked on BG pastures, and weaned 1 Oct. Cows were sorted at weaning into 3 groups of BCS: <=4 (LO); 5 (ME); or >=6 (HI). After weaning, FAL calvers grazed BG pastures without supplement (SUP), and WIN calvers grazed BG until 15 Nov, and thereafter on BG hay plus 2 kg per day SUP. At weaning, cow BCS was different (P<0.001) for each group with FAL BCS at 3.9, 5.1, and 6.5; and WIN BCS at 3.8, 5.0, and 6.3. Calving interval was similar within a calving season, but different (P<0.05) for WIN at 365 d and FAL at 375 d. Cows with different BCS at weaning varied (P<0.01) in body weight from 480 kg (LO) to 570 kg (HI). Cow BCS was different (P<0.001) at subsequent birth in FAL for each category of LO (5.5), ME (5.7), and HI (6.2); and different (P<.001) for WIN at LO 5.2, ME 5.5, and HI at 5.8. Rebreeding was similar for FAL vs WIN cow BCS at weaning with 90.5, 90.0, and 88%, respectively for LO, ME, and HI BCS. Brahman F-1 cows calving in FAL or WIN and with LO BCS at weaning regained BCS>5.2 on BG pasture or BG hay plus SUP by the time of the next calf for FAL (103 d) and WIN (132 d).